B is the midpoint of ac d is the midpoint of ce and ae =21 what is bd

Answers

Answer 1
Answer: bd = 1/2 ae
bd = 1/2 × 21 = 10.5

Related Questions

When x = -3 on the graph of y = 2|x| + 3 what will be the y-coordinate?A. -3 B. 3 C. -9 D. 9
Solve each quadratic equation by factoring and using the zero product property.10x + 6 = -2x^2 -2
1. The concession stand is selling hot dogs and hamburgers during a game. At halftime, they sold a total of 78 hot dogs and hamburgers and brought in $105.50. how many of each item did they sell if hamburgers sold for $1.50 and hot dogs sold for $1.25?
8 + 6t - 3t + t would equal 12t^3? First one gets Brainliest Answer!
Please help me with this and explain how you got the answer. :)

Four employees can wash 20 service vehicles in 5 hours. how long would it tke 5 employees to wash the same number of vehicles?

Answers

So the employee rate for washing cars turns out to be 4*5 = 20 man hours to wash 20 vehicles which is 1 vehicle per hour per employee. 
5 employees will wash 5 vehicles in 1 hour 
5 employees will wash 20 vehicles in 1*4 = 4 hours.

You paint 1313 of a wall in 1414 hour. At that rate, how long will it take you to paint one wall?

Answers

You paint 1313 of a wall in 1414 hour.
Now we need to find the rate in order you to paint one wall.

1313 : 1414 = 1 : X
1414 = 1313 X
X = 1.08

So the rate per one wall is 1.08 hours.

Solve the triangle.B = 73°, b = 15, c = 8
Select one:
a. C = 35.9°, A = 71.3°, a ≈ 15.2
b. C = 30.7°, A = 76.3°, a ≈ 15.2
c. C = 30.7°, A = 76.3°, a ≈ 21.3
d. Cannot be solved

Answers

Using the sine law of triangles to solve for angle C:

b / sin B = c / sin C

C = arcsin (c * sin B / b)
C = 30.7°

Since interior angles of a triangle always add up to 180
°, we can use this to solve for angle A:

angle A = 180
° - 73° - 30.7°
angle A = 76.3
°

Having solved for angle A, we can solve for side a using the sine law.

a / sin A = b / sin B

a = b * sin A / sin B
a = 15.2

Therefore, the correct answer is B.

G(x) = 3x -1. Find x such that g(x)= 2​​0​.g​(x)= 3x+1. Find x ​​​such that g(x)= 22​​​​.​

g(x)= ​2x-5. Find g(1/2) and g(a)=9​​​​​​9.
g(x)=x+5/2. Find g(3), g(0), g(-3) and g(x)=0​​​​​​​​​​

Please solve this quickly. I need it right now​​​​​. No silly answer will not be allowed.

Answers

Step-by-step explanation:

i. 3x-1=20

or, 3x= 21

x= 7

ii. 3x+1= 22

3x= 21

x= 7

iii. 2x-5=99

2x= 104

x=52

iv. g(3)= 3+5/2= 11/2

g(0)= 0+ 5/2=5/2

g(-3)= -3+5/2 = -1/2

x+5/2= 0

so, x= -5/2

The steps below show the incomplete solution to find the value of y for the equation 6y − 3y − 5 = −3 + 23:Step 1: 6y − 3y − 5 = −3 + 23
Step 2: 6y − 3y − 5 = 20
Step 3: 3y − 5 = 20

Which of these is most likely the next step?
3y = 4

3y = 15

3y = 25

3y = 5

Answers

Answer with Step-by-step explanation:

We have to find the value of y for the equation:

6y − 3y − 5 = −3 + 23:

Step 1: 6y − 3y − 5 = −3 + 23

Solving the right hand side of the equation gives Step 2

Step 2: 6y − 3y − 5 = 20

combining the terms of y on left hand side gives step 3

Step 3: 3y − 5 = 20

Now, Adding 5 on both sides, we get

3y-5+5=20+5

⇒ 3y=25

Hence, most likely the next step is:

3y=25

3y=25

final answer y=25/3

Evaluate each expression for s = 2 and t = 5

-4(s)²+t³÷5

Answers

sub
s=2
t=5

-4(2)^2+(5^3)/5
PEMDAS

exponents first sice parentahsees are already simplified
2^2=4
5^3=125
now we have
-4(4)+125/5
multiplication or division
-4 times 4=-16
125/5=25

nowe we have
-16+26
9

answer is 9
-4(s)^2 + t^2 ÷ 5
-4(2)^2 + 5^2÷ 5=
-4x4 + 25/5 =
-16 + 5 = -11